Intangible Capital and Labor Productivity Growth: Revisiting the Evidence - Felix Roth; Ali Sen (University of Hamburg, Chair of International Economics, 2021)
This contribution analyzes the impact of intangible capital on labor productivity growth across countries at the aggregate and sectoral levels by employing an econometric growth-accounting approach. First, our results show that intangible capital deepening accounts for around 40 percent of labor productivity growth at both the aggregate and sectoral level. Second, we find that this positive impact of intangible capital on productivity growth at both levels of aggregation is driven by investments in economic competencies, the only intangible group not covered in the national accounts. Third, our results reveal deep sectoral heterogeneities regarding investments and productivity effects of different intangible types. These findings have important implications for future EU industrial policies and are directly relevant to the EU's efforts to close its productivity gap with the US.
Keywords: C23; E22; L16; L60; L80; O47; O52; 330; intangible capital; labor productivity growth; cross-country sectoral panel analysis; manufacturing; market services; EU